2021
DOI: 10.3389/fphar.2021.770667
|View full text |Cite
|
Sign up to set email alerts
|

Sempervirine Mediates Autophagy and Apoptosis via the Akt/mTOR Signaling Pathways in Glioma Cells

Abstract: The potential antitumor effects of sempervirine (SPV), an alkaloid compound derived from the traditional Chinese medicine Gelsemium elegans Benth., on different malignant tumors were described in detail. The impact of SPV on glioma cells and the basic atomic components remain uncertain. This study aimed to investigate the activity of SPV in vitro and in vivo. The effect of SPV on the growth of human glioma cells was determined to explore three aspects, namely, cell cycle, cell apoptosis, and autophagy. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…An in vivo experimental result showed that sempervirine (4.0 and 8.0 mg/kg, i.p. , for 28 days) significantly decreased the growth of glioma cancer by 44.76% and 61.26%, respectively 50 . In human hepatocellular carcinoma, sempervirine (0.1, 0.5, and 1.0 μM) induced HepG2 cells apoptosis and blocked the cell cycle in the G1 phase, accompanied by the upregulation of p53 and the downregulation of cyclin D1, cyclin B1, and CDK2.…”
Section: Pharmacological Activitymentioning
confidence: 96%
“…An in vivo experimental result showed that sempervirine (4.0 and 8.0 mg/kg, i.p. , for 28 days) significantly decreased the growth of glioma cancer by 44.76% and 61.26%, respectively 50 . In human hepatocellular carcinoma, sempervirine (0.1, 0.5, and 1.0 μM) induced HepG2 cells apoptosis and blocked the cell cycle in the G1 phase, accompanied by the upregulation of p53 and the downregulation of cyclin D1, cyclin B1, and CDK2.…”
Section: Pharmacological Activitymentioning
confidence: 96%
“…Therefore, inhibiting the activity of AKT is of significant importance for the treatment of GBM. For instance, Sempervirine induces G2/M phase cell cycle arrest and promotes cell apoptosis by inhibiting the AKT/mTOR signaling pathway [ 38 ]. Besides, inhibiting the AKT signaling pathway can enhance the sensitivity of GBM to TMZ [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, autophagy is taken as a potential therapeutic target into consideration for both glioma prevention and therapy, whereas its role and mechanisms require further clarification. Recently, a number of studies have shown that downregulation of the pro‐survival mTOR pathway can prevent autophagosome fusion to lysosomes at later time points to induce the autophagic death of glioblastoma cells 19–21 . In addition, transcriptome‐based network analysis and follow‐up experimental research have shown that the expression of autophagy‐related pathway proteins, such as mTOR, was significantly reduced by hirudin treatment in rats with unilateral ureteral obstruction 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of studies have shown that downregulation of the pro‐survival mTOR pathway can prevent autophagosome fusion to lysosomes at later time points to induce the autophagic death of glioblastoma cells. 19 , 20 , 21 In addition, transcriptome‐based network analysis and follow‐up experimental research have shown that the expression of autophagy‐related pathway proteins, such as mTOR, was significantly reduced by hirudin treatment in rats with unilateral ureteral obstruction. 22 However, whether the inhibitory effect of hirudin on human glioma involves autophagy has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%